Phytochemical Profile, Antilipase, Hemoglobin Antiglycation, Antihyperglycemic, and Anti-Inflammatory Activities of Solanum elaeagnifolium Cav. - Mohammed Bouslamti; Amal Elrherabi; El Hassania Loukili; Omar M. Noman; Ramzi A. Mothana; Mansour N. Ibrahim; Rhizlan Abdnim; Meryem Slighoua; Mohamed Bouhrim; Mohamed Bnouham; Badiaa Lyoussi; Ahmed Samir Benjelloun (Applied Sciences, 2023)
In the present investigation, the phenolic compounds of Solanum elaeagnifolium were identified, and the plant’s anti-lipase and anti-glycation effects on hemoglobin were discovered through in vitro experiments, as well as its short-term antihyperglycemic and anti-inflammatory effects. The chemical compound composition was detected using HPLC-DAD, the anti-lipase activity was tested in vitro using 4-nitrophenyl butyrate as a substrate, and the antiglycation activity of the plant extracts was also tested in vitro using a haemoglobin model. The antihyperglycemic effect was determined by inhibiting pancreatic α-amylase and α-glycosidase activity and performing an in vivo glucose tolerance test on normal rats, and the anti-inflammatory activity was determined by inducing paw inflammation with carrageenan. In both the SEFR (fruit) and SEFE (leaf) extracts, chromatographic analysis revealed the presence of quercetin 3-O-β-D-glucoside, rutin, and quercetin. SEFR inhibited the pancreatic lipase enzyme more effectively, with an IC50 of 0.106 ± 0.00 mg/mL. S. elaeagnifolium extracts demonstrated significant antiglycation activity, with 3.990 ± 0.23 mg/mL of SEFE and 3.997 ± 0.14 mg/mL of SEFR. When compared to positive and negative controls, plant extracts had very significant anti-diabetic and anti-inflammatory effects. The findings in this study and previous research on this plant encourage us to investigate other pharmacological activities of this plant besides its duiretic, cictrisant, and anti-ulcer activity.